VAN DIJK'S CRITICAL DISCOURSE ANALYSIS OF PRABOWO SUBIANTO'S VICTORY DECLARATION SPEECH IN THE 2019 ELECTIONS - Fathur Rahmi Afdhila; Abdur Razzaq; Manalullaili Manalullaili (Program Studi Komunikasi dan Penyiaran Islam UIN Raden Fatah Palembang, 2023)
Discourse is a way of discussing ideas with the public in order to influence public perception of the ideas put forward. Prabowo Subianto's speech contained meaning constructions and language strategies to represent ideas that language users believed to be understood by the audience. The purpose of this study is to find out the description of critical discourse analysis in Prabowo Subianto's victory declaration speech in the 2019 election using the Teun A. Van Dijk critical discourse analysis method which consists of three dimensions of analysis namely text, social cognition and social context. This research islibrary research and the approach used is descriptive qualitative with data analysis techniques using critical discourse analysis model Teun A. Van Dijk. The results of this study show the delivery and call for Indonesian unity. In the speech there was Prabowo Subianto's ideology regarding his big plans for Indonesia, such as making Indonesia a nation with a strong economy and adhering to the 1945 Constitution and Pancasila. Through the victory declaration speech, Prabowo Subianto tried to appeal enthusiastically to build Indonesia into a prosperous nation through several programs that he campaigned before the 2019 election